2022
DOI: 10.1108/mf-07-2022-0330
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the intellectual structure and demystifying the research trend of cross listing: a bibliometric analysis

Abstract: PurposeThis study aims to conduct a comprehensive bibliometric analysis to determine the intellectual structure of cross-listing studies and suggests a road map for future research in this field.Design/methodology/approachA step-by-step procedure was carried out. With the help of a defined search string, 580 articles from reputed journals have been retrieved from the Scopus database. Bibliographic coupling and keyword analysis were executed to understand the current research scenario and future research direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 131 publications
1
33
0
Order By: Relevance
“…Here, the study's results show that 459 papers were produced by the first group of 18 journals, 458 articles by the second group of 78 journals and 451 articles by the third group of 310 journals. Consistent with Batra et al (2022b), the result suggested that research on ownership structure did not appropriately support Bradford's law. There is a slight difference between the observed distribution of journals and Bradford's law distribution results.…”
Section: Analysis Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Here, the study's results show that 459 papers were produced by the first group of 18 journals, 458 articles by the second group of 78 journals and 451 articles by the third group of 310 journals. Consistent with Batra et al (2022b), the result suggested that research on ownership structure did not appropriately support Bradford's law. There is a slight difference between the observed distribution of journals and Bradford's law distribution results.…”
Section: Analysis Methodsmentioning
confidence: 85%
“…The primary goal of the review study is to clarify the current state of knowledge in a given research topic and point out areas where further research is still needed (Batra et al, 2022b).…”
Section: Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before using R-Studio, the R programming language was used to manipulate data, statistical analysis, and data visualization. R-Studio, or the Integrated Development Environment (IDE), is a platform to hold various packages using the R language to analyze text mining and matrix (Batra et al, 2022;Gupta et al, 2022;Hassan, 2022).…”
Section: Methodsmentioning
confidence: 99%